ENERGO-ECONOMICS PAYBACK INVESTMENT CALCULATION MODELLING OF GAS-STEAM COMBINED CYCLE POWER PLANT - Strušnik, Dušan; Avsec, Jurij (Journal of Energy Technology, 2023)
The paper deals with energo-economic payback calculation modelling of the combined gassteam cycle operation, demonstrating the basic characteristic properties of cycle behaviour in different operating regimes and calculating the payback period of the investment. The calculation of the payback period of the investment is based on the calculation of the net present value and with actual obtaining data sets from a recently built gas-steam combined cycle power plant. The results of the calculation modelling show that the gas-steam combined cycle power plant can achieve a useful efficiency of up to 88% in the back-pressure operation of the steam turbine. The useful efficiency of the gas turbine is up to 40%. The payback period of the investment depends on the investment costs, the quantity and market price of the consumed fuel, the quantity and market price of the generated electricity and thermal energy. The results show that with a price ratio fuel/electricity of 0.36, the payback period of the investment is 4 years, with a price ratio fuel/electricity of 0.54, the payback period of the investment is as much as 17 years.